“Diseño Arquitectónico de una Estación de Bomberos en la Parroquia Santa Rosa del Cantón Ambato - Masabanda Tiban, Christian Javier (2025)
This thesis focuses on the architectural design of a fire substation in the Santa Rosa parish of the Ambato canton, with the purpose of addressing the growing need for adequate infrastructure to respond to emergencies, particularly forest fires. This problem has been identified as a priority in the Development and Territorial Planning Plan (PDOT) of the canton and by the Ambato Fire Department, due to the notable industrial and economic growth that the Santa Rosa parish has experienced. The project proposes a fire substation that combines functionality, comfort and operational efficiency, focused on improving response times and ensuring the safety of staff and the community. For its development, a qualitative methodology was adopted that includes semi-structured interviews, field analysis and documentary review, with special emphasis on the strategic selection of the land and compliance with national regulations, such as the Ecuadorian Technical Standards (NEC), and international regulations, such as the NFPA recommendations. The architectural proposal includes operational, administrative and rest areas, designed to optimize functionality and promote staff well-being. It also incorporates solutions such as the efficient use of energy and local materials. In conclusion, the architectural design of this fire substation represents a significant contribution to risk management and the protection of the population, contributing to the comprehensive development of the Santa Rosa parish and its surrounding areas.